Pelatihan CAD/CAM bagi Guru Teknik Permesinan di SMK Negeri Kletek Kabupaten Malaka untuk Peningkatan Kompetensi Pemodelan dan Produksi Media Ajar: Training on CAD/CAM for Mechanical Engineering Teachers at SMK Negeri Kletek, Malaka Regency to Enhance Competence in Modeling and Teaching Media Production - Fahrizal, Fahrizal; Manesi, Damianus; Mau, Sealtial; Priyono, Priyono; Bianome, Wofrid Erlista; Atok, Laurensius Kristo; Liu, Mikhael Dendy Robertus; Susanto, Yohanes Karoberd Yugi; Lengo, Edwinurius Berlinus; Mnune, Edwin Deriston (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The rapid development of modern industry requires mastery of Computer-Aided Design (CAD) and Computer-Aided Manufacturing (CAM) as essential competencies for the technical workforce. However, in remote and border areas such as Malaka Regency, vocational school teachers, particularly in the field of mechanical engineering at SMK Negeri Kletek, still face limited facilities and minimal access to technology and up-to-date training. To address this issue, a community service program was conducted in the form of CAD/CAM training using Autodesk Inventor software on June 10–11, 2025, at the school's mechanical workshop. The method consisted of three stages: preparation, which included coordination and a needs assessment with the partner school; training, covering theoretical introduction, practical modeling, CAD–CAM integration, and simulation of part production; and evaluation, carried out through pre-tests and post-tests, observation of valuable skills, and participant feedback. The results indicated a significant improvement in teacher competence, with the average score increasing from 45 in the pre-test to 82 in the post-test. Moreover, teachers were able to produce digital models of machine components that can be utilized as teaching media in the classroom. This activity demonstrates that a practice-based and simulation-driven approach can effectively enhance teacher skills.